Empty Chair untuk Remaja dengan Post-Traumatic Stress Disorder - Nahdliyati Nur Muhammad; Ika Yuniar Cahyanti (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This report aims to understand the psychological dynamics of a 17-year-old female adolescent who has experienced post-traumatic stress disorder (PTSD) as a result of physical and verbal abuse from her parents since childhood. The study was conducted at LPPT Widya Prasthya, Makassar, using a qualitative approach and case study method. Data collection was conducted through in-depth interviews, observations, home visits, and psychological assessments using tools such as the DAP, BAUM, HTP, SSCT, WAIS, DASS, and BDI-II. The results indicated that the client was experiencing PTSD characterized by avoidance symptoms, emotional outbursts, hypervigilance, and feelings of worthlessness, which impacted her social and academic functioning. Interventions were conducted over seven sessions using the empty chair technique from the existential-humanistic approach, accompanied by relaxation and psychoeducation for clients and parents. Intervention outcomes showed significant progress, with clients able to recognize and express their emotions, resolve internal conflicts with traumatic figures, and begin building more open relationships with their parents. Protective factors such as family support, adequate intellectual capacity, and access to mental health services also supported the client's recovery. Thus, the client's prognosis is positive.